Using Role Play to Teach Internal Controls in a Basic Auditing Course - Cheuk, Sharon (INTI University College, 2009)
The auditing of business operating cycles is often taught using the textbook approach, whereby students are presented with basic theory, followed by an explanation and demonstration of relevant audit procedures. This instructional case describes a role playing exercise that has been successfully used at Universiti Malaysia Sabah (UMS) to provide students with hands-on experience b testing internal controls in a revenue cycle audit. Although this activity involved relatively little formal lecture input from staff, there was a significant Investment of staff time in writing the role play document and in organizing and facilitating the role play exercise. Students’ feedback was largely encouraging In that a high level of enjoyment and understanding of the material was observed.